A behavioural theory of economic development : the uneven evolution of cities and regions - Huggins, Robert; Thompson, Piers (United Kingdom : Oxford University Press, 2021)
This book establishes a novel behavioural theory of economic development to illustrate differences in human behaviour across cities and regions, both individually and collectively, are a significant deep-rooted cause of uneven development within and across nations.
Formerly CIP.
Includes bibliographical references (pages 257-298) and index.
usc 24/10/2022
Ref.
Keywords: Economic development; Regional economic disparities; Rural development; Cities and towns--Growth; Europe